Case report: Surgical management of ileal duplication cyst in a cat: a case report and review of the literature - Kim, Kihoon; Kim, Jaehwan; Kim, Hwiyool (Frontiers in Veterinary Science, 2023)
A 6-year-old castrated, mixed breed cat presented with vomiting, anorexia, and lethargy. Ultrasonography and computed tomography revealed a round, well-marginated structure closely associated with the ileum proximal to the ileocolic junction. Exploratory laparotomy revealed a mass originating from the distal end of the ileum, close to the ileocolic junction. The mass did not interact with the intestinal lumen. Excisional biopsy with omentalization was performed without small intestinal resection to preserve the ileocolic junctions. Histopathological examination confirmed the presence of an enteric duplication cyst. The cat recovered uneventfully from surgery and remained asymptomatic postoperatively. No recurrence was identified 4 months after surgery. Enteric duplication cysts are uncommon congenital anomalies that originate in the gastrointestinal tract. They could either be communicating or non-communicating with the intestinal lumen. Enteric duplication cysts can be symptomatic or asymptomatic. Enteric duplication cysts associated with the esophagus, duodenum, and jejunum have also been reported in cats. However, to the best of our knowledge, this is the first reported case of an enteric duplication cyst in the feline ileum. Thus, enteric duplication should be considered a differential diagnosis in cystic masses of the ileum.